Trade in Ideas: Outsourcing and Knowledge Spillovers - Sebastian Benz; Mario Larch; Markus Zimmer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
Inspired by the theory of variety-expanding product innovation we derive a testable relationship of outsourcing on the growth rate of knowledge. We estimate this relationship with a firm-level dataset, which is a unique match of PATSTAT patent data and theAmadeus dataset. We find evidence that forward spillovers are stronger than backward spillovers, where forward spillovers are defined as spillovers going down the value chain from producers to users of intermediate inputs. Moreover, we conclude that interindustry spillovers are stronger than intra-industry spillovers. This holds when considering only the more important forward spillovers as well as when considering both directions of knowledge flows
Keywords: C21; F14; O30; O52; 330; Outsourcing; knowledge spillovers; patents.